ATM-Based Voting System - Omotunde, Ayokunle A.; Ejenobor, Martin; Onuiri, Ernest E.; Wumi, Ajayi; Aaron, Izang; Olubukola, Adekola (Asian Journal of Electrical Sciences, 2021)
Voting is a critical element of any election which involves the processes of electing leaders or representatives into positions of authority in a democratic system of government. In most developing countries of the world, this process is usually marred with challenges of confidentiality, Integrity, availability and auditability such as falsification of results, identity theft, stolen of ballot boxes, multiple voting problems, over voting, and electoral fraud. This paper presents a framework for Automated Teller Machine-based voting system that solves the aforementioned challenges of the current voting system by using the existing Automated Teller Machines and debit cards issued for voting. Going further to implement the solution proposed in this paper will enhance and guarantee the credibility of the electoral processes and show a true reflection of the wishes of the people.